Iris positioning technique by using face symmetric measurement tool on the custom ocular prosthesis: a case report - Rilinda, Femy; Tamin, Haslinda Z.; Ritonga, Putri Welda Utami (Indonesian Journal of Prosthodontic, 2021)
Loss of eye can have a major psychological impact on the patient. To overcome this problem, an ocular prosthetic must have been fabricated similar with the natural eye. Various techniques are documented to determine the symme- trical bilateral iris position; these methods can be subjective and have no measurement guidelines. A 20-year-old male patient came to the Prosthodontic Clinic of Dental Hospital Universitas Sumatera Utara with the diagnosis is post enucleation socket syndrome. Determination of the iris position using the face symmetric measurement-tool by focus to the vertical and horizontal lines of the facial symmetry guide. Confirm the alignment of the vertical lines by connecting the trichion–glabella–subnasal–gnathion guide points so that they vertically divide the two sides of the face, then the two horizontal lines by connecting the left-right cheilon with the mesial-distal canthus of the right and left eyes. This tool is like a face mask with vertical and horizontal guidelines connecting the symmetrical guide points of the face accompanied by centimeters and millimetres making it easy to measure distances and sizes of the iris symmetrically. The use of this tool has given good results in determining the position of the iris because its simplicity and can see facial symmetry.